An analysis of the evolution of Chinese cities in global scientific collaboration networks: Manuscript prepared for special issue on 'China's internationalization and changing role in the world' - Zhan Cao; Ben Derudder; Liang Dai; Zhenwei Peng (ZFW - Advances in Economic Geography, 2023)
This paper examines the emergence of China - now the world's largest source of scientific publications - in global science from the perspective of the connectivity of its major cities in interurban scientific collaboration networks. We construct collaboration networks between 526 major cities (including 44 Chinese cities) for 2002-2006 and 2014-2018 based on co-publication data drawn from the Web of Science. Both datasets are analyzed using a combination of different centrality measures, which in turn allows assessing the shifting geographies of global science in general and the shifting position of Chinese cities therein in particular. The results show that: (1) on a global scale, the bipolar dominance of Europe and North America has waned in light of the rise of Asia-Pacific and especially China. Most Chinese cities have made significant gains in different centrality measures, albeit that only a handful of cities qualify as world-leading scientific centers. (2) The rise in connectivity of Chinese cities is therefore geographically uneven, as cities along the East Coast and the Yangtze River corridor have become markedly more prominent than cities in other parts of China. The uneven trajectories of Chinese cities can be traced back to changing institutional, economic, and geopolitical contexts. (3) Evolution in the global scientific collaboration network exhibits strong 'Matthew Effects', which can be attributed to the path-dependent nature of knowledge production and preferential attachment processes in scientific collaboration.
Keywords: 330; China; Evolution; Global science; Network analysis; Network centrality; Scientific collaboration